Relational Leadership and Stakeholder Co-Production for Quality Education: Advancing SDG 4 and SDG 17 in Catholic Secondary Schools in Eastern Indonesia - Remigius Missa; Maria Veronika Roesminingsih; Bambang Sigit Widodo (Journal of Current Studies in SDGs, 2027)
Objective: Investigates how school principals convert relational managerial capabilities into stakeholder co-production that advances Sustainable Development Goal 4 and Sustainable Development Goal 17  across three Catholic secondary schools in Eastern Indonesia. Method: A focused secondary thematic analysis was conducted on a qualitative multi-site case-study dataset generated through in-depth interviews, participant observation, and documentary analysis. Within-site and cross-site analyses examined communication, listening, motivation, recognition, delegation, stakeholder participation, and partnership mobilisation. Results: Six interdependent practices emerged: establishing relational safety, facilitating dialogic sensemaking, institutionalising participatory planning, delegating according to competence, integrating recognition with reciprocal accountability, and mobilising family-school-foundation-community partnerships. These practices strengthened teacher commitment, programme ownership, student support, access to additional resources, and community legitimacy. Context shaped enactment: the resource-constrained school depended more heavily on external networks, whereas the seminary school embedded participation within a shared formation mission. Novelty: The study proposes a relational co-production pathway in which trust and stakeholder participation operate as organisational infrastructure rather than supplementary programmes. The model explains how relational leadership connects school-level managerial practice with quality education (SDG 4) and sustainable partnerships (SDG 17) in faith-based and resource-differentiated settings.